ANALISIS KEPUASAN PENGGUNAAN MEDIA PEMBELAJARAN ONLINE PADA SEKOLAH AL-FURQON PALEMBANG MENGGUNAKAN EUCS (END USER COMPUTING SATISFACTION) & METODE DELONE AND MCLEAN - Prasvianto, Eki; Wardani, Kiky Rizky Nova (SISKOMTI: Jurnal Sistem Informasi Komputer dan Teknologi Informasi, 2021)
Al Furqon High School Palembang uses google classroom online learning media, especially when social distancing is imposed due to the Covid-19 pandemic. The use of online learning media is used to stop the spread of the corona virus. To determine the level of teacher and student satisfaction in the variable of using online learning media used to measure this level of satisfaction is the EUCS method variable and the Delone and McLean model. The variables used are content, accuracy, format, ease of use, timeliness, system quality, service quality. The population in this study were teachers and students, the number of samples in this study was 71 respondents. The sampling technique used is that after processing the data, the significance value of the content variable user satisfaction is 0.000 <0.05 and the tcount is 2.725 > ttable 1.999. The timeliness variable is 0.000 <0.005 and tcount 3.794 > ttable 1.999. And the Delone & McLean variable which has a significance on user satisfaction is the service quality variable of 0.000 <0.05 and tcount 6,000 > ttable 1.999 partially positive and has a significant effect on user satisfaction.